Association of oxytocin receptor gene polymorphisms with autism spectrum disorder in Bengali of Bangladesh population (Asian Journal of Medical and Biological Research, 2020)
Autism spectrum disorder (ASD) is a group of sex-biased neurodevelopmental disorders characterized by core deficits in social interaction, communication and behaviors. Several lines of evidence indicate that oxytocin signaling through its receptor (OXTR), is vital in a wide range of social behaviors and role of OXTR polymorphism in ASD development has also been established in several populations. Therefore, an attempt was taken to determine whether genetic variations in the oxytocin signaling system contribute to ASD susceptibility in a part of Bangladeshi (BEB) population. We have investigated the role of OXTR polymorphisms (rs53576, rs2254298, rs2228485 and rs237911) in ASD development through PCR-RFLP method, based on case studies. A significant frequency (p = 0.027) for OXTR ‘rs53576AA’ risk genotype was found to be associated with ASD which is consistent with the previous study in Chinese but Caucasian and Japanese population. Besides, no significant association has been found for other OXTR variants (rs2254298, rs2228485 and rs237911) in this study. Understanding of these significant association with ASD development could be open a new clue aimed at clinical marker development for ASD diagnosis and treatment in future.Asian J. Med. Biol. Res. June 2020, 6(2): 176-186